Aplicação de plantas daninhas na biofumigação para o controle de Meloidogyne javanica - Segatto, Thalia Aparecida (2023)
Root-knot nematodes cause considerable damage to food production. One of the most used alternatives for their control is the use of chemical nematicides. In this way, new control practices are increasingly sought with efficiency and less environmental impact, like, for instance, the incorporation and biofumigation of non-host parts of plants or antagonistic plants. Biofumigation enables the release of compounds into the soil, many of them with potential nematicides. Weeds can be a significant problem in production and are often controlled and completely discarded from the production system. In this sence, the objectives of this work were to verify the potential of several weeds against M. javanica by aqueous extracts and emission of volatile organic compounds (VOCs), to evaluate the most promising ones against nematode eggs and in the biofumigation of the infested substrate and to identify the volatilome of the most efficient plants in the control of M. javanica. Initially, tests were carried out verifying extracts and VOC emissions from leaves of 18 plant species selected in the field by occurrence, family or previous studies against nematodes and other organisms. Initial screening was performed against second-stage (J2) juveniles of M javanica. The results indicated that all the tested plants showed a nematicidal effect against J2 both by contact with the extracts and by the emission of VOCs. However, leaves of guaco (Mikania cordifolia) and joá bravo (Solanum viarum) caused mortality close to 100% in J2. Leaf macerates and VOCs emitted by S. viarum and M. cordifolia also had a toxic effect on nematode eggs, reducing at least 35% of J2 hatching compared to control by water, reaching more than 70% reduction in M. cordifolia extract. In biofumigation with the different concentrations evaluated in the infested substrate, both species S. viarum and M. cordifolia reduced the infectivity and reproduction of nematodes with a high efficiency already at the concentration of 1.0% (m/m) in tomato seedlings. By GC/MS, volatilome of S. viarum and M. cordifolia were identified, which showed VOCs from several chemical groups, with emphasis on terpenes in M. cordifolia, and many VOCs from both species have already been described as toxic to other nematodes. such as β-pinene, ρCymene, Bicyclogermacrene, Trans-caryophyllene, Methyl Salicylate, Eugenol and Pentadecanal. This establishes the nematicidal potential of weeds in the incorporation and biofumigation of soil infested with M. javanica even at low concentrations, in addition to the possibility of prospecting for several nematicidal VOCs.